Analysis of Village Financial Management Information System in Monitoring Village Financial Management - Ramsilas, Topan; Marantika, Abshor; Zulher, Zulher (Dinasti Publisher, 2025)
Village financial management in Indonesia still faces significant obstacles, particularly in aspects of transparency, accountability, and efficiency. In Kampar Regency, Riau Province, the amount of village fund allocation has continued to rise, reaching approximately Rp156.5 billion in 2024. However, this increase has not been free from issues, especially related to monitoring mechanisms and the managerial capacity of village officials. To overcome these challenges, the government introduced the Village Financial System (SISKEUDES), a digital platform designed to facilitate bookkeeping, reporting, and financial oversight at the village level. This research aims to evaluate how SISKEUDES has been applied within the Community and Village Empowerment Office (DPMD) of Kampar Regency. A descriptive qualitative method was employed, combined with SWOT analysis. Data sources were obtained through field observations, document review, and interviews with key informants. Findings indicate that all villages (100%) in Kampar Regency have already adopted SISKEUDES. Nonetheless, its practical use has not reached the expected level due to several obstacles, such as weak internet connectivity, limited digital skills among village apparatus, and delays in certain technical operations. The SWOT analysis highlights strengths, including regulatory backing and full coverage of SISKEUDES implementation, while weaknesses include inadequate infrastructure and human resource capacity. Opportunities were found in the form of strong national policy direction and ongoing advances in digital technology, whereas threats involved risks to data security and reluctance from some local officials. Based on these results, the recommended strategies are: improving staff competence through continuous training, enhancing ICT infrastructure, enforcing standardized operating procedures (SOPs), and strengthening data protection. From a practical perspective, this study contributes directly to DPMD Kampar by supporting better monitoring of the village budget (APBDes) and encouraging greater citizen engagement. Theoretically, it enriches the discourse on digital-based public financial management systems at the local governance level.